2014
DOI: 10.1016/j.lungcan.2014.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive therapy for patients with non-small cell lung carcinoma and synchronous brain-only oligometastatic disease is associated with long-term survival

Abstract: Objectives Optimal therapy for patients with non-small cell lung carcinoma (NSCLC) presenting with synchronous brain-only oligometastases (SBO) is not well defined. We sought to analyze the effect of differing therapeutic paradigms in this subpopulation. Materials and Methods We retrospectively analyzed NSCLC patients with 1-4 SBO diagnosed between 1/2000 and 1/2011 at our institution. Patients with T0 tumors or documented Karnofsky Performance Status <70 were excluded. Aggressive thoracic therapy (ATT) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 27 publications
5
66
2
1
Order By: Relevance
“…All the included studies are retrospective observational cohort studies from 1999 to 2015, consisting of 668 synchronous oligometastatic NSCLC patients, among whom 227 (34.0%) received ATT. With regard to ATT regimens, Surgery only was the modality of ATT in one study (26), radiotherapy in one study (23), and surgery combined with radiotherapy or not in the five others articles (24,25,(27)(28)(29). When stratifying by oligometastatic state, single organ metastases was reported in five studies (24,(26)(27)(28)(29), of which four included only patients with brain-only metastases (24,(27)(28)(29).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…All the included studies are retrospective observational cohort studies from 1999 to 2015, consisting of 668 synchronous oligometastatic NSCLC patients, among whom 227 (34.0%) received ATT. With regard to ATT regimens, Surgery only was the modality of ATT in one study (26), radiotherapy in one study (23), and surgery combined with radiotherapy or not in the five others articles (24,25,(27)(28)(29). When stratifying by oligometastatic state, single organ metastases was reported in five studies (24,(26)(27)(28)(29), of which four included only patients with brain-only metastases (24,(27)(28)(29).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…For synchronous brain metastases, a recent study showed that patients with multiple metastases who received ATT had significantly improved survival vs. no-ATT, and this trend also was observed in those with a solitary metastasis (24). However, recent European guidelines did not recommend ATT for patients with more than one brain metastasis (34).…”
Section: Subgroup Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The five-year survival rate of lung cancer patients is approximately 18% [2]. Eighty-five percent of lung cancer patients were non-small cell lung cancer (NSCLC), whose five-year survival rate is about 21% [3]. The common types of NSCLC are adenocarcinomas and squamous cell carcinomas with five-year survival rates of 42.8% and 43.4% [4].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, when consider prognosis in stage IV disease, another significant aspect to consider is the site of metastases. In particular, brain or adrenal gland secondary lesion seem to be associated with prolonged survival rather than bone or liver ones (21,(29)(30)(31)(32)(33)(34)(35). Referring to the above risk factors, it is possible to stratify and identify patients who are candidates for aggressive local treatment.…”
Section: Oligometastatic Disease: State Of Artmentioning
confidence: 99%